Development and Evaluation of the Implementation of Guidelines for Healthier Canteens in Dutch Secondary Schools: Study Protocol of a Quasi-Experimental Trial - Evenhuis, Irma J. (Front Public Health, 2019)
Introduction: To encourage healthier food/drink choices, the “Guidelines for Healthier Canteens” were developed by the Netherlands Nutrition Centre. This paper describes (1) how we developed a plan to support implementation of the “Guidelines for Healthier Canteens” in Dutch secondary schools, and (2) how we will evaluate this plan on process and effect level. Materials and Methods: The implementation plan (consisting of several tools) was developed in cooperation with stakeholders. Barriers/facilitators to implement the guidelines were identified by 14 interviews and prioritized during one expert meeting. Thereafter, these barriers were translated into implementation tools using behavioral change methods and implementation strategies. The implementation plan consists of the tools: tailored advice provided via an advisory meeting and report, based on a questionnaire about the stakeholders'/school's context and the “Canteen Scan,” an online tool to assess the product availability and accessibility; communication materials; an online community; newsletters; a factsheet with students' wishes/needs. This implementation plan will be evaluated on process and effect in a 6-month quasi-experimental controlled design with 10 intervention and 10 matched control schools. Process outcomes will be measured: (1) factors affecting implementation and (2) the quality of implementation, both collected via a questionnaire among involved stakeholders. Effect outcomes will be collected pre/post-intervention with: (1) self-reported purchase behavior among around 100 students per school; (2) the “health level” of the school canteen. Linear and linear/logistic two-level regression analyses will be performed. Discussion: The implementation tools are developed by combining a theory and practice-based approach, with input from different stakeholders. If these tools are evaluated positive, it will support schools/stakeholders to create a healthier school canteen. Trial Registration: Dutch Trial register no.: NTR5922, date of registration June 20, 2016; METC no.: 2015.331; EMGO+ project number: WC2015-008.